Lack of resistance in Aedes vexans field populations after 36 years of Bacillus thuringiensis subsp. Israelensis applications in the Upper Rhine Valley, Germany - Becker, Norbert; Ludwig, Mario; Su, Tianyun (Journal of the American Mosquito Control Association, 2018)
Bacillus thuringiensis subsp. israelensis (Bti) has been widely and solely used against floodwater mosquitoes, mostly Aedes vexans, for 36 years in the Upper Rhine Valley by the German Mosquito Control Association. During this period, almost 5,000 tons of Bti formulations were applied to an area of approximately 400,000 ha. To investigate a possible resistance development after such a long-term and widespread application of Bti, the susceptibility of Ae. vexans larvae to Bti in 3 untreated (Lake Constance) and 6 treated areas on both sides of the Rhine within the Upper Rhine Valley was assessed by bioassays following World Health Organization guidelines. Comparing log-probit analyses, it was shown that neither the median lethal concentration (LC50 values) nor slopes of the probit lines of bioassays of the larvae deriving from treated and untreated areas showed significant differences. These results have been confirmed by resistance ratios, which varied from 0.80 to 1.12 in all tests. The results provided the evidence that no restistance in the target species Ae. vexans has developed in the areas of the Upper Rhine Valley, despite the large-scale use of Bti for 36 years.